Pemanfaatan Minyak Jelantah dan Limbah Kulit Pisang Sebagai Bahan Dasar Untuk Pembuatan Lilin - Risa Nurfadilah; Nurhamidah, Ai siti; Azizah, Adella Mariam; Sodiq, M.Fajar; Nurmilah, Nisa (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Cipelah Village is a village that has great potential in the field of agriculture, one of which is the number of banana trees. In addition, many mothers in Cipe village use cooking oil to cook food, so that waste oil is often found in household environments. Cooking oil has a danger to health and the environment. With the large number of banana trees in the Cipelah area causing a lot of banana peel waste, banana peel waste can be used as an adsorbent to purify waste cooking oil. The amount of waste of cooking oil and banana peel can be minimized by making candles. The purpose of this service is to utilize waste banana peel and waste cookin oil for making candles as well as increasing public knowledge about making candles from waste cooking oil. The method used in this service is a workshop, students explained about the use of banana peel waste and jelantah oil as making candles. Then after that there was a demonstration of students on how to make candles from cooking oil. Based on the results of the workshop, participants can practice how to make candles from cooking oil, so it can be concluded that participants experience an increase in knowledge related to making candles from cooking oil.